Leśne tropy Czesława Miłosza - Anna Szawerna-Dyrszka (Postscriptum Polonistyczne)
The theme of this article has been suggested by Miłosz himself, who published in his Subjects to Let (the second part of Roadside Dog) the short essay Las [The Forest]. Author plaits the net of associations connected with the forest, which leads to reflection that this apparently obvious and exploited by generations of poets topic can still produce various contexts: geographical, natural, economic, political, cultural and literary ones as well as those of symbolic, mythical, historical and biographical character. This last context leads back to Miłosz, as a consequence of the reflection that the forest serves as a kind of symbolical frame for many plots present in his life and creativity. From a biographical and literary point of view, the poet leaves the forest. However, in 1997 (when Roadside Dog was published), toward the end of his long life, Miłosz returns to the forest in his poetry. He writes a separate text about it. There is a wide range of forest traces (literal, metaphorical, symbolical) between those two moments. They can be noticed in other books by Miłosz.